Temperate Forest Soil Microbiomes and Their Assembly Processes are Modulated by the Interplay of Co‐Existing Tree Species Identity, Diversity and Their Mycorrhizal Type - Hafeez Ul Haq; Bala Singavarapu; Amelie Hauer; Nico Eisenhauer; Olga Ferlian; Helge Bruelheide; Tesfaye Wubet (Journal of Sustainable Agriculture and Environment, 2025)
ABSTRACT Recent studies have highlighted the significant role of tree species' mycorrhizal traits on forest soil microbial communities and their associated ecosystem functions. However, our understanding of how tree species richness in mono‐mycorrhizal (arbuscular mycorrhiza [AM] or ectomycorrhiza [EcM]) or mixed‐mycorrhizal (AM and EcM = AE) stands affects the rooting zone microbial community assembly processes remains limited. We investigated this knowledge gap using the MyDiv tree diversity experiment, which comprises plantings of AM and EcM tree species and their mixture in one‐, two‐, and four‐species plots. Soil microbiomes in the target tree rooting zone were analyzed using meta‐barcoding of the fungal ITS2 and bacterial 16S V4 rRNA regions. We examined the effects of plot mycorrhizal type, tree species identity and richness on microbial diversity, community composition, and microbial community assembly processes. We found that AM plots exhibited higher fungal richness compared to EcM and mixed mycorrhizal type (AE) plots, whereas tree species identity and diversity showed no significant impact on fungal and bacterial alpha diversity within mono and mixed mycorrhizal type plots. The soil fungal community composition was shaped by tree species identity, tree diversity, and plot mycorrhizal type, while bacterial community composition was only affected by tree species identity. EcM tree species significantly impacted both soil fungal and bacterial community compositions. Plot mycorrhizal type and tree species richness displayed interactive effects on the fungal and bacterial community composition, with AM and EcM plots displaying contrasting patterns as tree diversity increased. Our results suggest that both stochastic and deterministic processes shape microbial community assemblage in mono and mixed mycorrhizal type tree communities. The importance of deterministic processes decreases from AM to EcM plots primarily due to homogeneous selection, while stochastic processes increase, mainly due to dispersal limitation. Stochastic processes affected fungal and bacterial community assembly differently, through dispersal limitation and homogenous dispersal, respectively. In fungi, the core, intermediate and rare abundance fungal taxa were mainly controlled by both stochastic and deterministic processes whereas bacterial communities were dominantly shaped by stochastic processes. These findings provide valuable insights into the role of tree species identity, diversity and mycorrhizal type mixture on the soil microbiome community composition and assembly processes, highlighting the differential impacts on core and rare microbial taxa. Understanding the balance between deterministic and stochastic processes can help forest ecosystem management by predicting microbial community responses to land‐use and environmental changes and influencing ecosystem functions critical for ecosystem health and productivity.